HUBUNGAN PENGETAHUAN TENTANG HIPERTENSI DENGAN PERILAKU LANSIA DALAM PENCEGAHAN HIPERTENSI DI POSYANDU LANSIA DESA TEGAL WANGI KECAMATAN UMBULSARI KABUPATEN JEMBER - Brahmantio Chrisna Tobias (Jurnal Kesehatan dr. Soebandi, 2015)
Hypertension is a serious public health problem, because if it is not controlled it will develop and cause dangerous complications. The increase in hypertension cases, especially in developing countries is estimated to be around 80% in 2025 from a number of 639 million cases in 2000, estimated to be 1.15 billion cases in 2025. This study is a correlational study with a cross sectional approach in which researchers can search, explain relationship and test between 2 variables, namely the level of knowledge about hypertension with hypertension prevention behavior. The population in this study was 34 respondents, while the sample was 31 respondents. The sampling technique used is simple random sampling. The results of this study showed that the majority of respondents (51.6%) had less knowledge and a small proportion (12.9%) elderly were well-informed. While the hypertension prevention behavior of the majority (54.84%) of respondents behaved sufficiently and a small proportion (16.13%) of elderly people behaved well. Based on data analysis, it is known that there is a relationship between knowledge about hypertension and the behavior of the elderly in the prevention of hypertension. The conclusion of this study is that there is a relationship between knowledge about hypertension and the behavior of the elderly in the prevention of hypertension in Tegal Wangi Village, Umbulsari District, Jember Regency. Providing information by health workers about hypertension will have a big role in reducing the occurrence of hypertension. It is assumed that a person's behavior is a manifestation of everything he knows